Do high local customer and supply densities foster firm growth? - Andreas Behr; Christoph Schiwy; Lucy Hong (Review of Regional Research, 2023)
We analyze the effect of local supplier and customer densities on employment growth, using a~sample of 190.167em275German firms. We suggest a~new approach to estimating firm-specific customer and supply densities through combining input-output data from the German Federal Statistical Office and firm-level data from the Orbis database. Existing empirical analyses are primarily conducted on a~regional level, so that findings may depend on the regarded regional level and only provide limited insights into the existence and effects of agglomeration on growth at the firm-level. We use kernel density estimation to avoid the arbitrariness of spatial boundaries and scales, and find that the regional agglomeration patterns vary considerably between different sectors. Our econometric analysis reveals that input supplier and customer densities have a~statistically significant effect on firm growth and that the firms' age plays a~crucial role in analyzing agglomeration economies.
Keywords: L25; R11; C10; 910; Firm Performance; Agglomeration; Kernel density estimation; Regional Economics